Pendampingan Kegiatan Hari Peduli Sampah Nasional sebagai Upaya Peningkatan Kesadaran Lingkungan di Bank Sampah Pelita Surabaya - Najwa Dhakiro Rochmah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
Waste management remains a significant issue in urban areas, particularly in Gunung Anyar Tambak, Surabaya, due to the low level of public awareness. This community service program aims to enhance community awareness and participation through assistance in the National Waste Awareness Day (HPSN) activities at Bank Sampah Pelita. The method used is Participatory Action Research (PAR), with data collected through observation, interviews, and direct participation. The results indicate an increase in community participation and understanding of waste management, as well as the development of environmental awareness through educational and participatory activities. This program demonstrates that a participatory approach is effective in encouraging sustainable behavioral change in the community. The participatory approach has proven to be an effective method for driving sustainable social change in waste management in this region. These findings also show that with active community involvement, waste management can be carried out more efficiently and have an impact on positive social change in the long term.